The purpose and functionality of legislation regarding skills development within the formal sector viewed against the background of the historical causes of the skills deficit in South Africa - Van Zyl, Jeanne (Stellenbosch : Stellenbosch University, 2018)
Thesis (LLM)--Stellenbosch Univeristy, 2018.